“Let’s have a cup of tea” – Scandinavian crime fiction through Hungarian eyes. Zoltán Kőhalmi’s practical guide to crime writers - Soós, Anita (Folia Scandinavica Posnaniensia, 2023)
In recent decades, a wide range of Scandinavian crime novels have conquered Hungarian readers, providing a more sophisticated perspective on the existing image of Scandinavian cultures and societies, with their intriguing social content and appealing landscapes. This wave of crime fiction has not only contributed to a better understanding of Scandinavia, but also drawn attention to the genre itself, which culminated in a parody written by a Hungarian stand-up comedian, Zoltán Kőhalmi. In his incorporation of all the obligatory ingredients of Scandinavian crime novels, the comedian not only reuses the self-image that Scandinavian crime narratives convey, he pillories the genre requirements by exaggerating the use of the most well-known characteristics. The analysis of Kőhalmi’s satirical use of Scandinavian crime narratives serves as a case study for a closer understanding of conceptions of Scandinavia in contemporary Hungary.